UJI EFEKTIVITAS JUS BUAH JAMBU BIJI MERAH (Psidium guajava, Linn.) TERHADAP KADAR HEMOGLOBIN (HB) DARAH TIKUS PUTIH JANTAN GALUR WISTAR (Rattus norvergicus L.) - Sambou, Christel Nataniel (PHARMACON, 2014)
ABSTRACT Red guava (Psidium guajava Linn.) is trusted by the public as a drug which serves to increase blood hemoglobin levels. This study aimed at determining the effect of increased volume of red Guava fruit juice on blood hemoglobin levels of white male Wistar rats (Rattus norvegicus L.). This type of research is experimental laboratory using the male Wistar rats which were divided into 5 treatment groups. Treatment group 1 (KP1) were administered with aquadest, KP2 were administered with sangobion, KP3 were administered with Guava fruit juice 2 mL/bw, KP4 were administered with guava fruit juice 2.5 mL/bw and KP5 were administered with guava fruit juice 3 mL/bw. Each treatment administered orally, 3 times daily for 3 days. Data were analyzed by paired t-test and One Way ANOVA. The result shows that red guava fruit juice has the influence to increase the blood hemoglobin levels, which is based on the significant differences with KP3 and KP4 but there is no significant difference with KP2 on the blood hemoglobin levels of the male wistar rats. Key words : Psidium guajava Linn, Rattus novergicus L, Hemoglobin (Hb) ABSTRAK Jambu biji merah (Psidium guajava Linn.) dipercaya oleh masyarakat sebagai obat untuk meningkatkan kadar hemoglobin darah. Penelitian ini bertujuan untuk mengetahui pengaruh dan hubungan peningkatan volume pemberian jus buah Jambu biji merah (Psidium guajava Linn.) terhadap kadar hemoglobin darah tikus putih jantan galur wistar (Rattus norvegicus L.). Jenis penelitian ini ialah eksperimental laboratorium yang dibagi dalam 5 kelompok perlakuan. Kelompok perlakuan (KP1) 1 diberi aquades, KP2 diberi larutan sangobion, KP3 diberi jus buah Jambu biji 2 mL/KgBB, KP4 diberi jus buah Jambu biji 2,5 mL/KgBB dan KP5 diberi jus buah Jambu biji 3 mL/KgBB. Masing-masing perlakuan diberikan secara peroral, 3 kali sehari selama 3 hari. Data dianalisis dengan uji-t data berpasangan dan uji analisis varians satu arah. Hasil penelitian menunjukkan jus buah Jambu biji merah memberikan pengaruh peningkatkan kadar hemoglobin darah yang berdasarkan uji statistik KP5 memiliki perbedaan yang signifikan dengan KP3 dan KP4 tetapi tidak ada perbedaan yang signifikan dengan KP2 terhadap kadar hemoglobin darah tikus putih jantan galur wistar. Kata kunci : Psidium guajava Linn, Rattus novergicus L, Hemoglobin (Hb)